A quantas anda o ethos camponês?: estratégias de reprodução social de jovens rurais - Souza, Bruno Lacerra de (2019)
The research is part of Brazilian Rural Sociology studies, focusing on the dynamics related to rural youth in agrarian reform settlements. The objective is to analyze how a lifestyle, a peasant habitus, is presented in the life projects and strategies of social reproduction developed by rural youths with their families. The empirical field consists of two rural settlements located in São Paulo State. Reunidas - Promissão / SP and Sepé Tiarajú - Serra Azul / SP, chosen according to their distinct characteristics. Respectively: a Federal Settlement Project (PA) and a Sustainable Development Project (PDS), located in different state regions (center-west of São Paulo and northeast of São Paulo), with different periods of occupation, connections with social movements, territorial origin of its occupants, size of the land and number of settled families. In these territories, I conducted semi-structured interviews, based on the qualitative method, as well as systematic observations, recorded in a field diary, audio and photo recordings. In previous researches it was found that we are facing a transformation in the rural world and that different arrangements and strategies are created for the permanence of young people settled in the countryside, these strategies have changed the social relations and the way in which the settlements are organized in past years. The analysis shows that these strategies can be observed in work in the city, in fairs, in involvement with cooperatives and with institutions that promotes rural development policies, in informal jobs or in studies seeking a placement on the market. The purpose of these precarious strategies is often posed as the possibility of maintaining life in the settlement, whether by contributing financially to the maintenance of the family, or by migrating daily between countryside-city to obtain a higher level of income. However, I observed that the link with the land and the territory is the guiding point of the strategies. In a context of constant transformations in the rural areas, specific social dynamics arise, in which rural youth are the protagonists. This research focus in these new social dynamics that consolidate rural youth as a category of studies, enabling the analysis of their way of life and the understanding of their main challenges.